Menilai Peran Pendidikan Dalam Membentuk Karakter Dan Kredibilitas Individu - Putri Rahminda; Aziva Umairoh; Witri Islaura W (Pusat Riset dan Inovasi Nasional, 2023)
Education is one of the main pillars in the development of individual character and credibility. It not only imparts knowledge, but also plays an important part in shaping an existent’s values, ethics, tone-confidence, and integrity. Building ethics in education is an trouble to form individualities who have moral values and good geste. Education also has a part in creating quality and competitive scolars. Education can give the chops, knowledge and capabilities demanded by individualities to face the challenges of the times. Education can also increase creativity, invention and entrepreneurship in individualities. This composition will explore the important part of education in shaping individual character and credibility, as well as its impact in various aspects of life